2019
DOI: 10.1029/2018gl080260
|View full text |Cite
|
Sign up to set email alerts
|

Observed Spatiotemporal Changes in the Mechanisms of Extreme Water Available for Runoff in the Western United States

Abstract: This paper presents the first study to identity, in historical records, regional changes in the mechanisms of extreme water available for runoff (W). We used a quality‐controlled Snowpack Telemetry data set (1979–2017) combined with the nonparametric regional Kendall test to examine changes in annual maximum W under four hydrometeorological conditions (melt only/rain‐on‐snow/all melt/all melt plus rainfall) over the mountainous regions of the western United States. Under a warming climate, our analyses indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 50 publications
2
28
2
Order By: Relevance
“…Figures 9a and 9b. The largest increases in the western United States occur in the high-elevation mountains that have not been affected by ROS in the past, especially the Upper Cascades in the PNW, which is consistent with the finding in Yan et al (2019). The greatest decreases occur in the coastal western United States, especially the middle-and low-elevation west facing barriers of the Sierra Nevada and the Cascades, where declines in snow accumulation and increases in rainfall intensity (which dilute ROS runoff contribution ratio) will occur in the future.…”
Section: Water Resources Researchsupporting
confidence: 89%
“…Figures 9a and 9b. The largest increases in the western United States occur in the high-elevation mountains that have not been affected by ROS in the past, especially the Upper Cascades in the PNW, which is consistent with the finding in Yan et al (2019). The greatest decreases occur in the coastal western United States, especially the middle-and low-elevation west facing barriers of the Sierra Nevada and the Cascades, where declines in snow accumulation and increases in rainfall intensity (which dilute ROS runoff contribution ratio) will occur in the future.…”
Section: Water Resources Researchsupporting
confidence: 89%
“…Berghuijs et al () explored the dominant flood‐generating mechanisms across the continental United States and found that snowmelt and ROS events were more robust predictors of the flooding response than rainfall over the western United States. This is further confirmed by Yan et al (), Yan, Sun, Wigmosta, Skaggs, Leung, et al () who found that the standard precipitation‐based intensity‐duration‐frequency curves often significantly underestimate extreme events in snow‐dominated environments, suggesting a critical role of snow in flooding in those environments. With a warming climate, ROS‐driven flood risk is projected to increase significantly in many western United States river basins with more frequent ROS events at high elevations where seasonal snowpack persists even in a warmer climate (Musselman et al, ).…”
Section: Introductionsupporting
confidence: 65%
“…By differentiating the precipitation phase using the change in SWE, the authors (Yan et al, 2018) also identified the dominant mechanism of extreme W at these sites, and found significant regional differences in flood-generating mechanisms across the WUS, e.g., the maritime regime is ROS dominated, and the continental regime is snowmelt dominated. The authors (Yan et al, 2019b) confirmed that this regional variability is associated with climate variability across the WUS, which includes air temperature, solar radiation, and atmospheric humidity. In the maritime regime that features high humidity, latent energy can warm the falling precipitation through condensation, leading to more frequent ROS events (Harpold and Brooks, 2018).…”
Section: Ng-idf Curves Vs Prec-idf Curvesmentioning
confidence: 64%
“…Global warming will lead to a shift in rain-snow ratio and increase soil freeze-thaw cycles, resulting in more frequent ROS events and higher flood risk at higher elevations in the future (Beniston and Stoffel, 2016;Musselman et al, 2018;Li et al, 2019). Using the BCQC SNOTEL data, the authors (Yan et al, 2019b) examined the changes in snow process and frequency of ROS events over 1979-2017. They found statistically significant trends toward declining and earlier snowmelt over the WUS.…”
Section: Nonstationary Ng-idf Curves Under Climate Changementioning
confidence: 99%